On request of we develop dedicated variants of ACE calculator - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
Draft versions are highly appreciated by AAK and the coffee company; now in the phase of gathering data on specific operations within the boundaries of these companies.